Factors inspiring employees at technical universities to make healthy food purchasing decisions - Ahamat, Amiruddin; Abdullah, Mohamed Ali; Ismail, Albert Feisal @ Muhd Feisal; Jaafar, Adib Akram (Universal Publishers, 2024)
Health is a major value in modern society. Obesity and other health problems are becoming more common in both high and low-income countries. These phenomena also have an impact on consumer purchasing decisions for healthy foods. The primary goal of this study is to determine the elements that influence customers' purchasing decisions for healthy foods. Design/methodology/approach: This survey was carried out among Malaysian staff at a public university. The survey research approach was used to acquire the data. The sample included 145 male and 120 female volunteers, ranging in age from 25 to 50 years. Findings: The results showed that knowledge and perceived risk have a positive relationship with purchase decisions made by both male and female employees. Understanding basic customer needs gives food marketers a better understanding of how men and women make healthy food purchasing decisions. Research limitations/implications: In order to make the results more reliable, it is recommended that future research distribute and collect data from whole Malaysia. Practical implications: This alerts food marketers to the possibility of a marketing approach to improve their market share. Originality/value: Understanding fundamental customer needs through research is extremely conclusive since it provides food marketers with extra insight into how men and women consumers make healthy food purchasing decisions.